1988
DOI: 10.1073/pnas.85.6.1849
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of contractile force in muscle fibers by antibody to myosin subfragment 2.

Abstract: Polyclonal antibody directed against the subfragment-2 region of myosin was purified by affinity chromatography. Skinned muscle fibers that had been preincubated with antibody were able to sustain only 7% of the active isometric force generated by control fibers. The effect of antibody on force production could not be accounted for by inhibition of ATP turnover.The classical rotating-head sliding filament model for force generation in activated muscle fibers (1-3) proposes that the force-generating event resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 17 publications
(17 reference statements)
1
16
0
Order By: Relevance
“…The large myosin head movement may not readily fit into the contraction model based on the myosin head rotation, and possibly would result either from cooperative action of myosin two heads (20,21) or from shortening of myosin subfragment-2 region (22,23). Much more experimental work is needed to clarify the myosin head movement responsible for muscle contraction.…”
Section: Discussionmentioning
confidence: 99%
“…The large myosin head movement may not readily fit into the contraction model based on the myosin head rotation, and possibly would result either from cooperative action of myosin two heads (20,21) or from shortening of myosin subfragment-2 region (22,23). Much more experimental work is needed to clarify the myosin head movement responsible for muscle contraction.…”
Section: Discussionmentioning
confidence: 99%
“…Polyclonal antibodies against the S-2 region of chicken pectoralis myosin produced in rabbit (rabbit anti-chicken S-2) and polyclonal antibodies against the S-2 region of rabbit psoas myosin produced in goat (goat anti-rabbit S-2) were prepared and purified as described (5). Rabbit myosin S-2 was isolated (13) and further purified by calcium precipitation (5).…”
Section: Methodsmentioning
confidence: 99%
“…The helix-coil model proposes that melting within subfragment-2 (S-2; the a-helical tail segment of heavy meromyosin) is triggered and generates force when the actin-attached cross-bridge swings away from the thick filament surface (3,4). In earlier work (5), it was shown that purified anti-S-2 antibody can markedly depress the isometric tension generated by skinned psoas fibers. The reduction in tension (to about 7% ofcontrol fibers) occurs in the absence of any direct effect on the ability of S-1 to undergo cyclic interaction with actin as measured by the ATPase of antibody-treated fibers.…”
mentioning
confidence: 99%
“…Helical and random coil structures of the S-2 hinge region are expressed as straight and zig-zag shapes, respectively [7]. -activated myofibrillar shortening [11,12]. In 1992, he asked me to work together using his anti-S-2 antibody, and we made the experiments to be described later with unexpected results.…”
Section: Proposal Of the Helix-coil Transition Theory By Harringtonmentioning
confidence: 99%